The Electronic Silk Road - ANUPAM CHANDER (Yale University Press, 2013)
The Silk Road linking the ancient world’s civilizations wound through deserts and mountain passes, traversed by caravans laden with the world’s treasures. The modern Silk Road winds its way through undersea fiber-optic cables and satellite links, ferrying electrons brimming with information. This electronic Silk Road makes possible trade in services heretofore impossible in human history. Radiologists, accountants, engineers, lawyers, musicians, filmmakers, and reporters now offer their services to the world without passing a customs checkpoint or boarding a plane. Like the ancient Silk Road, which transformed the lands that it connected, this new trade route promises to remake the world Today the people of the world are engaged in international trade with a greater intensity than ever before in human history. The subjects of international trade, too, are far more personal than ever before. They implicate our habits and hobbies, our travels, our communication, our friends, our politics, our health, and our finances. As our lives increasingly are reflected online, the range of activities subject to international trade grows. Services now join goods in the global marketplace, with workers in developing countries able to participate in lucrative Western markets despite immigration barriers and Western enterprises able to reach a global audience, often free of tariffs or local bureaucracies.